2018
DOI: 10.1002/cncr.31600
|View full text |Cite
|
Sign up to set email alerts
|

Frequent PTEN loss and differential HER2/PI3K signaling pathway alterations in salivary duct carcinoma: Implications for targeted therapy

Abstract: BACKGROUND Patients with advanced primary and recurrent salivary duct carcinoma (SDC), a rare and lethal malignancy, have limited therapeutic options. Novel small molecule agents aimed at targeting critical signaling associated with SDC tumorigenesis may lead to new therapeutic options in patients with these tumors. The HER2/PI3K axis, an important oncogenic pathway, has been targeted for therapy in several solid tumors. Currently, little is known on the role and clinical implications of alterations of the HER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 68 publications
2
18
0
Order By: Relevance
“…Several studies have reported frequent loss of PTEN expression, detected via IHC or FISH analysis, in up to 51% of SDC . In head and neck squamous cell carcinoma, tumor cells with PTEN loss were shown to be commonly resistant to pan‐PI3K inhibitors; however, in vitro studies have shown promising results for targeted PI3K therapy in SDC cells . Finally, the discovery of a TBL1XR1‐PIK3CA fusion, which has been reported to result in overexpression of the complete PIK3CA protein, in one of our cases further supports the important role of PIK3CA in the oncogenesis of SDC …”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Several studies have reported frequent loss of PTEN expression, detected via IHC or FISH analysis, in up to 51% of SDC . In head and neck squamous cell carcinoma, tumor cells with PTEN loss were shown to be commonly resistant to pan‐PI3K inhibitors; however, in vitro studies have shown promising results for targeted PI3K therapy in SDC cells . Finally, the discovery of a TBL1XR1‐PIK3CA fusion, which has been reported to result in overexpression of the complete PIK3CA protein, in one of our cases further supports the important role of PIK3CA in the oncogenesis of SDC …”
Section: Discussionsupporting
confidence: 74%
“…Besides PIK3CA mutations, loss of PTEN activates the PI3K pathway and thus may represent another potential target. Several studies have reported frequent loss of PTEN expression, detected via IHC or FISH analysis, in up to 51% of SDC . In head and neck squamous cell carcinoma, tumor cells with PTEN loss were shown to be commonly resistant to pan‐PI3K inhibitors; however, in vitro studies have shown promising results for targeted PI3K therapy in SDC cells .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations